PUBLIC OPINION SURVEY ON SELECTED PROBLEMS OF ROAD SAFETY (Perner's Contacts, 2012)
First part of paper briefly describes the methodology and procedure for implementing public opinion survey that was focused on selected road safety problems of citizens, carried out in selected regions of the Central Europe with support of project SOL – Save our lives. Second part of paper presents evaluating survey outcomes related to travel preferences, mobility habits and public attitudes towards main problems and risk factors on road safety in Zilina region.
Keywords: road safety, survey, Zilina region